2007
DOI: 10.1007/s11832-007-0010-z
|View full text |Cite
|
Sign up to set email alerts
|

The management of Legg-Calvé-Perthes’ disease: Is there a consensus?

Abstract: Purpose The aim of the study was to find out whether or not there is consensus among experienced pediatric orthopaedists about the management of certain clinical scenarios in Legg-Calvé-Perthes' disease. Methods A questionnaire was sent to all 297 members of the European Paediatric Orthopaedic Society (EPOS) describing four cases of Legg-Calvé-Perthes' disease (LCPD) with two X-rays each and a short description of the clinical scenario. Two of the patients were younger and two were older than six years of age.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…Some authors [7,[11][12][13][14]18] have reported that if such treatment is initiated in the phase of fragmentation, there is a possibility to correct or eliminate some risk signs (primarily femoral head subluxation and limited hip abduction), which then additionally improve later results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some authors [7,[11][12][13][14]18] have reported that if such treatment is initiated in the phase of fragmentation, there is a possibility to correct or eliminate some risk signs (primarily femoral head subluxation and limited hip abduction), which then additionally improve later results.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographic assessment in preoperative, immediate postoperative and final evaluation periods, and classifications according to CE angle [1], phase of the disease by Hirohashi-Menelaus [11,12], containment by Klisić-Menelaus [24], Catterall group grading and presence of risk signs [2,24], as well as on the basis of Herring's classification [12,13] were performed. Functional findings were evaluated according to the Harris hip score [10].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this classification Several publications have demonstrated better clinical outcomes with surgical intervention for groups B and B/C after the age of 8 years. 9,10 Several surgical procedures have addressed patients with the advanced stage of the disease; these include femoral and pelvic osteotomies. 11 Both procedures change the anatomy of the hip joint, which may hinder future joint arthroplasty.…”
Section: Introductionmentioning
confidence: 99%